Pengaruh Capital Expenditure Terhadap Respon Investor Pada Perusahaan Sektor Industri Infrastruktur Pada Tahun 2014 - 2018 - Lordy Pasya Jorghi; Juniarti Juniarti (Business Accounting Review, 2020)
Research in investor respond has been done many times before, but they do not have consistent results. The sample used in this research are the companies listed in Indonesian stock exchange in the period of 2014–2018. The investor respond in this research is measured by cummulative abnormal return (CAR). This research also uses leverage and firm age as specific characters for the companies used. The result shows that capital expenditure does not have an effect investor respond. The variable of leverage has a positive effect on investor respond, on the other hand firm age does not have an effect on profitability